Drought response analysis based on cross wavelet transform and mutual entropy - Yanling Li; Yunliang Wen; Hexin Lai; Qiqi Zhao (Alexandria Engineering Journal, 2020)
Drought exerts a significant impact on the sustainable development of social economy. For sustainable water use and rapid drought response, it is very meaningful to explore the correlation between meteorological drought and hydrological drought. This paper investigates the features of drought evolution based on cross wavelet transform (XWT) and mutual entropy. The meteorological drought was measured by the standardized precipitation index (SPI), while the hydrological drought was evaluated by the standardized runoff index (SRI). The research data were collected from hydrological stations and meteorological stations in the Yellow River basin of Henan Province, China. The main conclusions are as follows: (1) Both meteorological drought and hydrological drought had obvious periodicity, especially on the scale of 2–4a. (2) The evolution of meteorological drought varied greatly from place to place; through the study period, Henan province did not suffer any extreme drought, though the drought situation in the western region has an aggravating trend. (3) Hydrological drought has a strong positive correlation with meteorological drought, and generally lagged behind meteorological drought by 1–2 months in the study area. The research results lay a good basis for drought response in the Yellow River basin.